Effects of remote language teaching strategies on oral performance at the University of Costa Rica during the COVID-19 pandemic : voices from the Western Branch - Brenes Barrantes, Hazel Ariana 1997-; Brenes Barrantes, Melissa 1998-; Solano Murillo, Pamela 1997-; Vargas Madrigal, José David 1999-; Sevilla Morales, Henry 1986- ([San Ramón, Alajuela, Costa Rica], 2022)
Due to the COVID-19 pandemic, Costa Rican higher educational institutions had to switch from face-to-face lessons to an emergency remote teaching modality. Teachers started researching new strategies and activities to apply in their classes because they, as well as many of their students, were not prepared for the new online teaching challenges. In Costa Rica, by mid- 2021, no empirical studies were available about the effects of remote teaching strategies on students' oral performance. Thus, this research seeks to analyze the perceptions on the effects of remote language teaching strategies on junior students' oral performance at the English teaching majors of the University of Costa-Western Branch (UCR-WB). To develop this investigation, an explanatory sequential mixed method design was adopted, which involved a two-phase execution of the project. For the first, quantitative stage, a sample of 36 junior students from the Oral Communication VI course of the English Teaching Majors at UCR-WB participated by completing a questionnaire. For the second, qualitative stage, a semi-structured interview was administered to five of the participants from the first stage that were selected in order to explain some interrogatives derived from the quantitative phase. The findings show that the majority of informants expressed that remote teaching has positively affected their academic performance.
Proyecto de graduación (licenciatura en enseñanza del inglés)--Universidad de Costa Rica. Sede de Occidente, 2022
Keywords: Universidad de Costa Rica -- Sede de Occidente; ESTUDIANTES DE LENGUAS EXTRANJERAS -- INVESTIGACIONES -- COSTA RICA; INGLES -- EDUCACION EN LINEA -- EVALUACION; EDUCACION A DISTANCIA; COMPETENCIA Y DESEMPEÑO (LINGUISTICA) -- EVALUACION